2022
DOI: 10.3390/ma15114025
|View full text |Cite
|
Sign up to set email alerts
|

Multi Expression Programming Model for Strength Prediction of Fly-Ash-Treated Alkali-Contaminated Soils

Abstract: Rapid industrialization is leading to the pollution of underground natural soil by alkali concentration which may cause problems for the existing expansive soil in the form of producing expanding lattices. This research investigates the effect of stabilizing alkali-contaminated soil by using fly ash. The influence of alkali concentration (2 N and 4 N) and curing period (up to 28 days) on the unconfined compressive strength (UCS) of fly ash (FA)-treated (10%, 15%, and 20%) alkali-contaminated kaolin and black c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Khan et al 32 adopted the MEP‐based algorithm to calculate the strength of the fly‐ash‐treated alkali‐contaminated soils using 384 datasets with four different input parameters. The study concluded that the developed model had an R ‐value and RMSE of 0.937 and 18.271, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al 32 adopted the MEP‐based algorithm to calculate the strength of the fly‐ash‐treated alkali‐contaminated soils using 384 datasets with four different input parameters. The study concluded that the developed model had an R ‐value and RMSE of 0.937 and 18.271, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cementitious materials have been created in a diverse variety, including self-compacting concrete (SCC) [ 4 , 5 , 6 ], high-performance concrete (HPC) [ 7 , 8 , 9 ], lightweight concrete (LWC) [ 10 , 11 , 12 ], and ultra-high-performance concrete (UHPC) [ 13 , 14 , 15 ]. These materials are chosen carefully based on the requisite mechanical properties as well as required durability and might be vulnerable to a variety of degradations in which the most detrimental effect is cracking in the matrix [ 16 , 17 , 18 ]. The appearance of these cracks can affect the lifespan of a structure and occurs due to various reasons [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These materials are chosen carefully based on the requisite mechanical properties as well as required durability and might be vulnerable to a variety of degradations in which the most detrimental effect is cracking in the matrix [ 16 , 17 , 18 ]. The appearance of these cracks can affect the lifespan of a structure and occurs due to various reasons [ 17 ]. One cause of cracking in the cementitious matrix is restrained shrinkage, which occurs during the shrinkage of structural elements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations